Pengembangan Profesionalisme Guru Melalui Administrasi Pendidikan Berbasis Kebutuhan Dan Strategi Era Society 5.0 - Zafira, Gyannina Mecca; Fatahilla; Khomis, Raman; Hidayatullah, Rully; Harmonedi (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
The development of professionalism in educational administration is key to addressing the challenges of the Society 5.0 era, where technology and digitalization dominate various sectors, including education. This article discusses the importance of a needs-based approach and relevant strategies for enhancing professionalism in educational administration. By analyzing the demands of the Society 5.0 era, educational administration is required not only to master managerial skills but also to adapt to technological advancements and understand the more complex educational needs. The main strategies proposed include continuous training, the use of digital technology, and collaboration among stakeholders. The ultimate goal is to ensure that educational administration can support the improvement of educational quality and respond to global challenges through a flexible, innovative, and adaptive approach. Thus, professionalism in educational administration will remain relevant and effective in achieving higher educational standards in the Society 5.0 era.